2011
DOI: 10.5539/ijbm.v6n9p134
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of Rural Poor Women through Small Entrepreneurship Development: The Case of Bangladesh

Abstract: The present paper deals with the performance and role of small entrepreneurship in socioeconomic development of rural poor women. The selected households for the study divided into three categories of enterprises, namely livestock and poultry, nursery & handicraft making. The sample size for this study was 90.Findings revealed that the average annual income generation per household of livestock and poultry, nursery, and handicraft enterprise groups were Tk 55080, Tk39558 and Tk35630 respectively. Average chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 1 publication
2
19
0
2
Order By: Relevance
“…WPD can have some positive outcomes, such as women’s increased participation in socioeconomic activities, which can in turn improve their status, independence, and health-seeking behaviors ( Ahmed et al, 2006 ; Dineen & Le, 2015 ; Hadi, 2001 , 2005 ; Hamad & Fernald, 2015 ; Kabir & Huo, 2011 ; Madhania et al, 2015 ; Nahar et al, 2011 ; Strobach & Zaumseil, 2007 ). An exclusive focus on WPD can, however, also create confusion and contradictions among men.…”
Section: Gender Inequality and Female-focused Development In Rural Bamentioning
confidence: 99%
See 1 more Smart Citation
“…WPD can have some positive outcomes, such as women’s increased participation in socioeconomic activities, which can in turn improve their status, independence, and health-seeking behaviors ( Ahmed et al, 2006 ; Dineen & Le, 2015 ; Hadi, 2001 , 2005 ; Hamad & Fernald, 2015 ; Kabir & Huo, 2011 ; Madhania et al, 2015 ; Nahar et al, 2011 ; Strobach & Zaumseil, 2007 ). An exclusive focus on WPD can, however, also create confusion and contradictions among men.…”
Section: Gender Inequality and Female-focused Development In Rural Bamentioning
confidence: 99%
“…WPD has also become a controversial issue connected to women’s vulnerabilities to higher workloads, marital conflict, and domestic violence. A few studies have reported that WPD can improve women’s income and health ( Dineen & Le, 2015 ; Hamad & Fernald, 2015 ; Kabir & Huo, 2011 ; Madhania, Tompkinsa, Jacka, & Fishera, 2015 ; Nahar, Banu, & Nasreen, 2011 ), whereas other studies reported that WPD may increase their workloads, family conflicts and exposure to domestic violence ( Angelucci, 2008 ; Ashraf Ali, 2014 ; Enloe, 2015 ; Hippert, 2011 ; Karim, Emmelin, Resurreccion, & Wamala, 2012 ; Sigalla & Carney, 2012 ).…”
mentioning
confidence: 99%
“…Bangladesh is mostly confined to a traditional societal setting where women are underprivileged; having a highly marginalized social position might create significant obstacles to developing their own businesses [20,26]. The prevailing socio-cultural norms and traditions in this country might constrain women's mobility and, thereby, their participation in business activities [11,27]. In fact, Bangladeshi women's business operations largely depend on patriarchy and religion [20,26].…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, it multiplied in geometric progression and chased by almost all the nations, particularly developing due to its plain, yet effectual structure. Several studies (Johansen and Nilsson, 2007;Kabir and Huo, 2011) have proven its verity, as an appropriate technique to empower the underprivileged and to enlarge their earning propensity. It is generally believed that the success of microfinance lies in its fundamental role of easy credit provision to poor section, economically active but financially constrained, that has been ignored by the moneymaking commercial sector for years.…”
Section: Introductionmentioning
confidence: 99%